1993
DOI: 10.1007/bf01974306
|View full text |Cite
|
Sign up to set email alerts
|

Carlavirus isolates from cultivated Allium species represent three viruses

Abstract: From 12 cultivated and mostly vegetatively propagated Allium species and varieties tested for carlavirus infections, 94 virus isolates were obtained which varied greatly on indicator hosts. Chenopodium amaranticolor, C. quinoa, Celosia argentea vat. plumosa 'Geisha', Nicotiana hesperis accession 67A and N. occidentalis accession P1 proved valuable for detection, isolation and propagation of part of the isolates. The latter three species are new experimental hosts for carlaviruses of Allium species. Other isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Onion yellow dwarf virus and Leek yellow stripe virus, respectively, were reported by those authors in the main garlic-producing regions, with incidence percentages ranging from 33 to 100% and from 34 to 98%. These results disagree with those found in other works (Van Dijk, 1993;Tsuneyoshi et al, 1998;Klukácková et al, 2007), which indicated that GarCLV is the most common virus infecting garlic.…”
Section: Departmentcontrasting
confidence: 99%
See 4 more Smart Citations
“…Onion yellow dwarf virus and Leek yellow stripe virus, respectively, were reported by those authors in the main garlic-producing regions, with incidence percentages ranging from 33 to 100% and from 34 to 98%. These results disagree with those found in other works (Van Dijk, 1993;Tsuneyoshi et al, 1998;Klukácková et al, 2007), which indicated that GarCLV is the most common virus infecting garlic.…”
Section: Departmentcontrasting
confidence: 99%
“…These differences could be due to different factors, such as resistance or tolerance of some garlic genotypes to GarCLV, or a lower aphid transmission efficiency of these viruses (Van Dijk, 1993). Considering that garlic is a species of exclusively agamic propagation, it is assumed that infected plants transmit the virus to successive generations, that the viruses will persist, and that the number of infected plants will increase gradually.…”
Section: Departmentmentioning
confidence: 99%
See 3 more Smart Citations